Signal and modulating role of enzymes of digestive glands - G. F. Korotko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To present literature data, to generalize cumulative experimental and clinical data of the author and his co-workers on effect of hydrolases of gastro-intestinal contents and circulating blood on digestive organs functions.Original positions. The role of enzymes of digestive glands is not limited to depolymerisation of nutrients, inactivation of antigens and bacteriostatic action. They carry out also signaling role in modulation of exo- and endocrine secretions of digestive glands and motor activity of gastro-intestinal tract. Proteinases realize effects through protease-activated receptors of four types which are localized on membranes of glandular cells, leiomyocytes, sensory terminals of afferent neurons and neuroendocrine producers of regulatory peptides, yielding direct and mediated morphofunctional effects.Conclusion. Enzymergic regulation of visceral functions, including sensory, alimentiry, protective, acts as new section of up-to-date science and, according to accumulated facts, is promising in gastroenterology, pancreatology, oncology, immunology and other segments of clinical medicine.